Estimating Risk of Postsurgical General and Geriatric Complications Using the VESPA Preoperative Tool - Min, Lillian (JAMA Surg, 2017)
IMPORTANCE: As greater numbers of older patients seek elective surgery, one approach to preventing postoperative complications is enhanced assessment of risks during preoperative evaluation. OBJECTIVE: To determine whether a geriatric assessment tool can be implemented in a preoperative clinic and can estimate risk of postoperative complications. DESIGN, SETTING, AND PARTICIPANTS: In this prospective cohort study, patients 70 years of age or older were assessed in a preoperative clinic for elective surgery from July 9, 2008, to January 5, 2011. Patients were screened using the Vulnerable Elders Surgical Pathways and Outcomes Assessment (VESPA) tool developed for this study. Patients were assessed on 5 preoperative activities of daily living recommended by the American College of Surgeons (bathing, transferring, dressing, shopping, and meals), history of falling or gait impairment, and depressive symptoms (2-item Patient Health Questionnaire). Patients also underwent a brief cognitive examination (Mini-Cog) and gait and balance assessment (Timed Up and Go test). A novel question was also asked as to whether patients expected they could manage themselves alone after discharge. Comorbidities and work-related relative value units (categorized into low, moderate, and high tertiles) were also collected. Multivariable logistic regression was performed to estimate risk of postoperative complications. Sustainability of VESPA over time was also evaluated. Medical record review was performed from December 11, 2012, to October 2, 2015, and data analysis was performed from November 15, 2015, to May 18, 2016. MAIN OUTCOMES AND MEASURES: Postoperative surgical and geriatric complications. RESULTS: Of the 770 patients evaluated, 736 (384 women and 352 men; mean [SD] age, 77.7 [5.7] years) underwent 740 operative procedures; of these patients, 711 had complete data for multivariable analysis. In our sample, 105 patients (14.3%) reported 1 or more difficulties with the 5 activities of daily living, and 270 of 707 patients (38.2%) foresaw themselves unable to manage self-care alone. A total of 131 of 740 patients had geriatric complications, and 114 of 740 patients had surgical complications; 187 of 740 patients (25.3%) had either geriatric or surgical complications. On multivariable analysis, the number of difficulties with activities of daily living (odds ratio [OR], 1.3; 95% CI, 1.0-1.6), anticipated difficulty with postoperative self-care (OR, 1.6; 95% CI, 1.0-2.2), Charlson Comorbidity score of 2 or more vs less than 2 (OR, 1.5; 95% CI, 1.0-2.3), male sex (OR, 1.6; 95% CI, 1.1-2.3), and work-related relative value units (moderate vs low: OR, 1.9; 95% CI, 1.1-3.3; high vs low: OR, 8.8; 95% CI, 5.3-14.5) were independently associated with postoperative complications (overall model area under the receiver operating characteristic curve, 0.77). With these results, a whole-point VESPA score used alone to estimate risk of complications also demonstrated excellent fit (area under the curve, 0.76). CONCLUSIONS AND RELEVANCE: Preoperative assessment of older geriatric patients is feasible in the general preoperative clinic and can help identify patients at higher risk of postoperative complications.